Desempenho bioeconômico e características de carcaça de cordeiros mestiços Dorper-Santa Inês e Dorper-Somalis brasileiro submetidos a um modelo de produção precoce - Souza, Daniel de Araújo (2011)
The experiment was conducted to evaluate the bioeconomic performance and the carcass traits of ½ Dorper-Santa Inês and ½ Dorper-Brazilian Somali lambs under an early production model. Twenty non castrated lambs were distributed in a completely randomized design with two treatments (genetic group) of ten replicates. In pre-weaning phase, the lambs were confined under creep feeding system with overnight breastfeeding, from 7th post-birth day until the weaning at 60 days old, when their followed to the finishing phase at feedlot with high concentrate diet. The lambs were slaughtered when achieved 3 mm of subcutaneous fat thickness, which was monitored and measured by ultrasonography. ½ Dorper-Santa Inês lambs were superior to body weight gain in pre-weaning and finishing phases, while the ½ Dorper-Brazilian Somali lambs were earlier as the growth and finishing. There was significant difference between genetic groups for hot carcass weight, chilled carcass weight, cooler shrink, ribeye area, carcass compactness index, hindlimb compactness index and cuts weight. However, ½ Dorper-Santa Inês and ½ Dorper-Brazilian Somali lambs had similar results for ribeye area:chilled carcass weight ratio and proportion of commercial cuts. ½ Dorper-Brazilian Somali lambs had greater subcutaneous fat thickness:chilled carcass weight and GR:chilled carcass weight ratios. From data of performance of the 20 crossbred lambs (weaning weight, average daily gain and dry matter intake) and of regression analysis (slaughter weight in function of the 3 mm subcutaneous fat thickness) was projected a feedlot for finishing of weaned lambs with static capacity for 100 animals by finishing cycle. The economic analysis showed positive results for all indexes evaluated. The compounds with highest influence on production cost of the feedlot were the purchase of weaned lambs and the feeding. ½ Dorper-Santa Inês and ½ Dorper-Brazilian Somali lambs have satisfactory results for performance and for production of quality sheep meat, beyond economic viability, under an early production model.